2017
DOI: 10.1155/2017/1342150
|View full text |Cite
|
Sign up to set email alerts
|

Four‐Week Consumption of Malaysian Honey Reduces Excess Weight Gain and Improves Obesity‐Related Parameters in High Fat Diet Induced Obese Rats

Abstract: Many studies revealed the potential of honey consumption in controlling obesity. However, no study has been conducted using Malaysian honey. In this study, we investigated the efficacy of two local Malaysian honey types: Gelam and Acacia honey in reducing excess weight gain and other parameters related to obesity. The quality of both honey types was determined through physicochemical analysis and contents of phenolic and flavonoid. Male Sprague-Dawley rats were induced to become obese using high fat diet (HFD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…During the 6-week treatment period, the obese rats that were treated with 500 mg/kg, 750 mg/kg, and 1000 mg/kg of SBH showed a significant reduction in body weight and BMI compared to the control obese rats. These findings correlate with those given by Chepulis et al (2009) [18] and Samat et al (2017) [15].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…During the 6-week treatment period, the obese rats that were treated with 500 mg/kg, 750 mg/kg, and 1000 mg/kg of SBH showed a significant reduction in body weight and BMI compared to the control obese rats. These findings correlate with those given by Chepulis et al (2009) [18] and Samat et al (2017) [15].…”
Section: Discussionsupporting
confidence: 93%
“…The possible mechanism contributing to the reduction of body weight gain in subjects treated with honey is the insulin-mimetic effects of hydrogen peroxide that is produced from the honey and increases metabolism rates [18]. Glucose oxidase enzyme might be responsible for hydrogen peroxide production from honey through glucose oxidation [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The honeys and the orlistat drug which elicited hepatotoxicity effects showed similar effects in significantly reduced levels of plasma glucose, triglycerides and cholesterol, obesity related parameters in rats. The authors suggested Gelam and Acacia honey are more effective than orlistat in obesity control through regulation of lipid metabolism [113]. The finding was supportive to the investigation on the renoprotective effect of Tualang honey on HCD fed rats.…”
Section: Honey In Relieving Multiple Facets Of Atherosclerosismentioning
confidence: 52%